Covariation of redox potential profiles and the water table level at peatland sites representing different drainage regimes: implications for ecological modelling - M. Koskinen; J. Anttila; V. Vranová; L. Holík; K. Roche; M. Vorenhout; M. Vorenhout; M. Pihlatie; R. Laiho (Biogeosciences)
Reduction–oxidation (redox) reactions are ubiquitous in nature and are responsible for the energy acquisition of all organisms. Redox reactions are electron transfer reactions that necessarily involve two participants: one being oxidised (electron donor) and one being reduced (electron acceptor).